Combined methods elucidate the multi-organ toxicity of cylindrospermopsin (CYN) on Daphnia magna. (1st May 2023) - He, Zhongshi; Chen, Youxin; Huo, Da; Gao, Jin; Xu, Yewei; Yang, Rui; Yang, Yiming; Yu, Gongliang
Abstract: Global water bodies are now at risk from inevitable cyanobacterial blooms and their production of multiple cyanotoxins, in particular cylindrospermopsin (CYN). However, research on the CYN toxicity and its molecular mechanisms is still limited, whilst the responses of aquatic species against CYN are uncovered. By integrating behavioral observations, chemical detections and transcriptome analysis, this study demonstrated that CYN exerted multi-organ toxicity to model species, Daphnia magna . The present study confirmed that CYN could cause protein inhibition by undermining total protein contents, and altered the gene expression related to proteolysis. Meantime, CYN induced oxidative stress by increasing reactive oxygen species (ROS) level, decreasing the glutathione (GSH) concentration, and interfered with protoheme formation process molecularly. Neurotoxicity led by CYN was solidly determined by abnormal swimming patterns, reduced acetylcholinesterase (AChE), and downward expression of muscarinic acetylcholine receptor (CHRM). Importantly, for the first time, this research determined CYN directly interfered with energy metabolism in cladocerans. CYN distinctively reduced filtration and ingestion rate by targeting on heart and thoracic limbs, which declined the energy intake, and could be further displayed by the reduction of motional strength and the trypsin concentration. These phenotypic alterations were supported by transcriptomic profile, including the down-regulation of oxidative phosphorylation and ATP synthesis. Moreover, CYN was speculated to trigger the self-defense responses of D. magna, known as "abandon-ship" by moderating lipid metabolism and distribution. This study, overall, comprehensively demonstrated the CYN toxicity and the responses of D. magna against it, which is of great significance to the advancements of CYN toxicity knowledge. Graphical abstract: Image 1 Highlights: Novel parameters ( s a P E I, R ‾ ) were developed for detecting detailed impairments. Solid evidence was found on the CYN neurotoxicity by AChE and related pathways. New-determined toxicity that CYN interfered with energy metabolism was reported. Reproduction strategies and mechanisms of D. magna against CYN were demonstrated.